Astrocytic and Neuronal Apolipoprotein E Isoforms Differentially Affect Neuronal Excitability - Konings, Sabine C.; Torres-Garcia, Laura; Martinsson, Isak; Gouras, Gunnar K. (Frontiers in Neuroscience, 2021)
Synaptic changes and neuronal network dysfunction are among the earliest changes in Alzheimer’s disease (AD). Apolipoprotein E4 (ApoE4), the major genetic risk factor in AD, has been shown to be present at synapses and to induce hyperexcitability in mouse knock-in brain regions vulnerable to AD. ApoE in the brain is mainly generated by astrocytes, however, neurons can also produce ApoE under stress conditions such as aging. The potential synaptic function(s) of ApoE and whether the cellular source of ApoE might affect neuronal excitability remain poorly understood. Therefore, the aim of this study was to elucidate the synaptic localization and effects on neuronal activity of the two main human ApoE isoforms from different cellular sources in control and AD-like in vitro cultured neuron models. In this study ApoE is seen to localize at or near to synaptic terminals. Additionally, we detected a cellular source-specific effect of ApoE isoforms on neuronal activity measured by live cell Ca2+ imaging. Neuronal activity increases after acute but not long-term administration of ApoE4 astrocyte medium. In contrast, ApoE expressed by neurons appears to induce the highest neuronal firing rate in the presence of ApoE3, rather than ApoE4. Moreover, increased neuronal activity in APP/PS1 AD transgenic compared to wild-type neurons is seen in the absence of astrocytic ApoE and the presence of astrocytic ApoE4, but not ApoE3. In summary, ApoE can target synapses and differentially induce changes in neuronal activity depending on whether ApoE is produced by astrocytes or neurons. Astrocytic ApoE induces the strongest neuronal firing with ApoE4, while the most active and efficient neuronal activity induced by neuronal ApoE is caused by ApoE3. ApoE isoforms also differentially affect neuronal activity in AD transgenic compared to wild-type neurons.